2020
DOI: 10.1057/s41307-020-00177-y
|View full text |Cite
|
Sign up to set email alerts
|

Private Supplementary Tutoring and Socio-economic Differences in Access to Higher Education

Abstract: Private supplementary tutoring in the form of preparatory courses to university entrance examinations, is present in Finland alongside public higher education (HE). We explore the participation in preparatory courses. Our data derives from the university undergraduate subsample (n=2,969) of a larger cross-sectional national survey targeting tertiary students. We found a strong association between the SES of the students and preparatory-course-participation rates. Preparatorycourse participation is also more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In these societies SE occupies at best remedial functions and does not support status attainment motives—at least at this point in time. A considerable SES gap in SE access only becomes apparent in Finland shortly before the transition to university, where a socially selective use of test preparatory courses is evident (Kosunen et al, 2020). Prior to such a significant allocation, societies with less selective schooling models sometimes even show a reversed SES gap in SE access, wherefore SE might actually help low-performing students to overcome their status disadvantages and reach higher levels of schooling.…”
Section: Discussionmentioning
confidence: 99%
“…In these societies SE occupies at best remedial functions and does not support status attainment motives—at least at this point in time. A considerable SES gap in SE access only becomes apparent in Finland shortly before the transition to university, where a socially selective use of test preparatory courses is evident (Kosunen et al, 2020). Prior to such a significant allocation, societies with less selective schooling models sometimes even show a reversed SES gap in SE access, wherefore SE might actually help low-performing students to overcome their status disadvantages and reach higher levels of schooling.…”
Section: Discussionmentioning
confidence: 99%
“…The focus was on courses targeting the 2017 entrance examinations in four selected fields of study: law, economics, medicine, and education (analysed earlier in Jokila, Haltia & Kosunen, 2019). The first three disciplines were selected 8 ECNU Review of Education because they are defined as status fields with competitive admission processes and these students largely come from upper-middle-class backgrounds (Kosunen, Haltia, Saari, Jokila & Halmkrona, 2020;Nevala, 1999). Education encompasses a more heterogeneous student body, but as the teaching profession is highly valued in Finnish society, the entrance is competitive.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Finally, the most significant agent operating in the market is prospective customers (i.e., the applicants and potentially their parents). In the Finnish context, the admitted students who participated in private tutoring are more often from higher socioeconomic backgrounds and have their fees paid for by their parents, while their counterparts from lower socioeconomic backgrounds work or borrow money to participate in a course (Kosunen et al, 2020). International studies have found that those students who participate in the courses are already in a good position in terms of gaining access to higher education (Pearce et al, 2018;Smyth, 2009).…”
Section: Marketizing Agenciesmentioning
confidence: 99%
See 2 more Smart Citations